The double-arch modified type-1b external skeletal fixator - Fitzpatrick, N.; Nikolaou, C.; Farrell, M.; Perry, K.; Girling, S.; Smith, T. J.; Yeadon, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
Objectives: To describe acute correction of antebrachial angular and rotational limb deformities (ARLD) using a new external skeletal fixator (ESF).Methods: Dogs that were presented with lameness caused by ARLD were treated by radial and ulnar osteotomies and acute realignment. A modified type-1b ESF incorporating double arches (DA-ESF) and a novel connecting configuration facilitated alignment with six degrees of freedom. Bilateral deformities were corrected surgically in the same session. Aseptic preparation of both antebrachii allowed comparison of limb alignment. Radiographic evaluation was performed using centre of rotation of angulation (CORA) methodology.Results: Thirty-five antebrachii (22 dogs) underwent surgery. Postoperative limb function was graded as good (n = 31), fair (n = 2), or poor (n = 2). Persistent medial carpal instability was associated with a suboptimal outcome. Postoperative radiographic images of the frontal and sagittal plane joint angles and elbow-to-carpus translation were compared with values that were reported in previous studies, and were within published reference ranges in most cases. Complications included delayed radial osteotomy union (n = 5), delayed ulnar osteotomy union (n = 2) and implant-associated morbidity (n = 3).Clinical relevance: A practical technique for acute correction of complex antebrachial ARLD is suggested, incorporating a new configuration of ESF. Putative limitations of radio-graphic planning using CORA may be compensated by careful attention to intra-operative visual and palpatory assessment.
Keywords: Antebrachial; external fixation; deformity; rotation; osteotomy